The rise of the dual labour market: fighting precarious employment in the new member states through industrial relations (PRECARIR). Country report: Latvia - Bukovska, Mara; Krumina, Marija; Vanags, Alf; Vildava, Linda (Bratislava, 2016)
"This report was financed by European Cmomission grant no. VS/2014/0534."